Utilizing RE-AIM to examine the translational potential of Project MOVE, a novel intervention for increasing physical activity levels in breast cancer survivors. Issue 4 (30th July 2018) - Pullen, Tanya; Bottorff, Joan L; Sabiston, Catherine M; Campbell, Kristin L; Eves, Neil D; Ellard, Susan L; Gotay, Carolyn; Fitzpatrick, Kayla; Sharp, Paul; Caperchione, Cristina M
Abstract : This research utilized the RE-AIM framework to gain a better understanding of translating an innovative physical activity intervention for breast cancer survivors' into community practice. Abstract: Translating effective research into community practice is critical for improving breast cancer (BC) survivor health. The purpose of this study is to utilize the RE-AIM framework to evaluate the translational potential of Project MOVE, an innovative intervention focused on increasing physical activity (PA) in BC survivors. A mixed-methods design, including a self-report questionnaire, accelerometry, focus groups, and interviews, was used to inform each RE-AIM dimension. Reach was evaluated by the representativeness of participants. Effectiveness was reflected by change in PA levels and perceptions of satisfaction and acceptability. Adoption was examined using participants' perceived barriers/facilitators to program uptake. Implementation was examined by participants' perceived barriers/facilitators to implementing the program. Maintenance was assessed by participant retention. Assessments occurred at baseline and 6-months. Mixed analysis of variance and content analysis were used to analyze the data. A total of 87 participants participated in Project MOVE and were demographically comparable to similar studies (Reach). Participants indicated high levels of program satisfaction (88%) and previously inactive survivors' significantly increased PA levels from baseline to 6-month follow-up (Effectiveness). Participants reported that a program focused on PA rather than disease helped them overcome barriers to PA (Adoption) and having leaders with BC and exercise expertise was essential to accommodate population specific barriers (Implementation). At 6-months, participant retention was 83% (Maintenance). Project MOVE is an acceptable, practical, and effective program for engaging BC survivors in PA and has the potential to be highly transferable to other populations and regions.